2020
DOI: 10.1186/s12885-020-6665-2
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA AFAP1-AS1 accelerates the progression of melanoma by targeting miR-653-5p/RAI14 axis

Abstract: Background: Melanoma is the most aggressive skin cancer that derived from pigment cells, accounting for the majority of the skin-cancer-related deaths. Despite great development and evolution have been made in surgery, radiotherapy and adjuvant chemotherapy, the prognosis of melanoma patients exhibited no significant improvement. Long noncoding RNAs (lncRNAs) are frequently dysregulated and involved in the development of cancers. LncRNA AFAP1-AS1 has been explored in various cancers, whereas its role and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 33 publications
(37 reference statements)
0
30
0
Order By: Relevance
“…7 Accumulating evidence suggests that lncRNAs execute critical roles in regulating pathological and physiological behaviors of cancer cells. [8][9][10][11] During cancer genesis and progression, cancerinhibiting and cancer-promoting cellular pathways are regulated by lncRNAs via direct or indirect effects, including gene expression regulation, chromatin remodeling, posttranscriptional modulation, and translational regulation. 12 Recent evidence has revealed the dysregulation of lncRNAs in breast cancer and has shown that aberrantly expressed lncRNAs are implicated in breast cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…7 Accumulating evidence suggests that lncRNAs execute critical roles in regulating pathological and physiological behaviors of cancer cells. [8][9][10][11] During cancer genesis and progression, cancerinhibiting and cancer-promoting cellular pathways are regulated by lncRNAs via direct or indirect effects, including gene expression regulation, chromatin remodeling, posttranscriptional modulation, and translational regulation. 12 Recent evidence has revealed the dysregulation of lncRNAs in breast cancer and has shown that aberrantly expressed lncRNAs are implicated in breast cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that lncRNAs can regulate various biological processes, such as proliferation, migration, invasion and apoptosis of melanoma cells ( 21 , 22 ). For instance, lncRNA lung adenocarcinoma associated transcript 1 expression is increased in melanoma via modulation of the miR-28-5p/RAP1B axis ( 23 ).…”
Section: Discussionmentioning
confidence: 84%
“…4,5 Previous studies reported that lncRNAs are dysregulated in different types of cancers and have critical effects related to cancer biology. [6][7][8][9] Some lncRNAs have been reported to be closely related to liver cancer pathology, progression, prognosis, and the maintenance of cancer stem celllike properties. 10,11 For example, LINC00668 up-regulation accelerates cell proliferation, migration, and invasion of HCC via targeting miR-532-5p/YY1 axis; 12 HAGLROS is highexpressed in HCC and its high expression is correlated with the progression of HCC by affecting cell proliferation, apoptosis, and autophagy via regulating miR-5095/ATG12 axis; 13 HCC patients with high-expressed lncRNA PDZD7 tend to show a poorer prognosis; PDZD7 promotes stemness properties and inhibits chemosensitivity of HCC via regulating the miR-101/EZH2/ATOH8 pathway.…”
Section: Introductionmentioning
confidence: 99%